(untitled) (Journal of the College of Education for Women, 2024)
Recently, there has been a great interest in ecological degradation and technological progress and its effects on the function of the natural ecosystem. These dangerous effects highlight the urgent need for eco-criticism as it presents a modern approach to analyzing and understanding literary works based on scientific evidence of ecology. Humans’ progress and control of the planet and its ecosystem cause disturbances, including the climate system. Eco-criticism challenges the concept of Anthropocene and advocates for a reshaping man’s centered attitude. The paper analyzes climate change as slow violence resulting from extreme weather patterns represented in melting glaciers due to human activities, which lead to global floods. These patterns inappropriately impact the most vulnerable entities: the Inuit people and the white polar bears, who contribute the least to greenhouse gas emissions. The current paper shows how theatre becomes an ecological activist, engaging in performances that address the ecological crisis while emphasizing the absence of ecological justice. Chantal Bilodeau’s Sila (2015) discusses the theme of the invisible threat of anthropogenic climate change caused by industrial progress and its insidious consequences on the indigenous people, ecosystem, and animals and calls for attention to climate justice in the global context.